Diencephalic storm in trauma patients: Is it really that rare - Andrew C Bright; Celia Y Quang; Scott G Blair; Nathan M Polite; Kaitlin M Alexander; Andrew Haiflich; C Caleb Butts; Yann-leei L Lee; Christopher M Kinnard; Maryann I Mbaka; Ashley Y Williams; Jon D Simmons (Open Journal of Trauma - Peertechz Publications, 2022)
Introduction: Diencephalic storm is characterized by extreme episodic catecholamine release in the presence of a stressor and it is usually refractory to standard antihypertensives. The treatment of choice during the crisis is propofol and the best preventative measure is to remove the stressor (i.e. ventilator).  Case presentation: A 32-year-old male sustained 2nd and 3rd degree burn to 25 percent of the body surface area that included a severe inhalation component. The patient was admitted to the Burn Intensive Care Unit at the Arnold Luterman Regional Burn Center in Mobile, AL. The patient had frequent episodes (3-5 per day) of severe agitation that were accompanied by extreme tachycardia of > 200 beats per minute and hypertension (280/140). The inciting event was often endotracheal suctioning, but less noxious stimulation also resulted in similar episodes. During these episodes, the patient had significantly elevated catecholamine levels that improved after extubation. The patient's symptoms were refractor to standard antihypertensives but immediately resolved when given propofol. Further episodes of the diencephalic storm were treated successfully with propofol. Once the patient was removed from mechanical ventilation, there were no further episodes.  Conclusion: Diencephalic Storm may be difficult to diagnose due to a lack of familiarity with this rare entity. Any patient with severe agitation combined with the effects of episodic large catecholamine surges should be considered to have Diencephalic Storm. The standard immediate treatment is propofol due to the lack of responsiveness of standard antihypertensives and the removal of the stressor.